Improving Student Learning Outcomes through Theatrical Application Methods - Saepuloh, Dadang; Estu Niana Syamiya; Putri, Eriza Eka (Jurnal Pedagogi dan Pembelajaran, 2025)
Economics learning in secondary schools often needs help improving student engagement and learning outcomes due to low motivation and the dominance of less effective traditional teaching methods. This requires a more innovative approach to enhance student motivation and academic achievement. The study aims to analyze the effectiveness of theatrical learning methods on learning outcomes and student motivation in economics subjects. The researcher used an experimental method with a quasi-experimental design as an analysis tool. The population in this study is 180 students in class X, with the technical determination of convenience sampling samples into 36 students selected to be the experimental and control groups. The analysis showed that the application of theatrical learning methods impacted student learning outcomes but did not show an increase in student learning motivation. These findings have implications for theatrical learning methods, hence the importance of innovation in teaching strategies to actively engage students. This can provide input for developing more effective curriculum and economic learning methods by combining theory and practice in daily life. Future researchers are advised to examine the influence of theatrical learning methods on student motivation by involving variables such as intrinsic motivation and individual learning styles. In addition, comparing theatrical methods with other methods, such as project-based learning, digital gamification, and collaboration, can expand the understanding of effectiveness in economics learning in high school.